Karakteristik Tepung Tulang Ikan Tuna Sirip Kuning (Thunnus albacares) sebagai Sumber Kalsium dengan Perlakuan Suhu Pengeringan yang Berbeda - Anhar Rozi; Nabila Ukhty (Jurnal FishtecH, 2021)
The raw material used in this study was yellowfin tuna (Thunnus albacares) bone from tuna fillet processing in tuna freezing company. The aimed of this study was produce bone meal as a source calsium. This research consited of two stage, first stage was making fish bone meal and second stage analysis of chemical, heavy metal, calsium and microbial content of fish bone meal. This study used different drying temperature treatment (90 oC, 100 oC, dan 110 oC), and than was analyzed descriptively. Yellowfin tuna (Thunnus albacares) bone meal which was drying temperature treatment at 110 oC had yield (19.37%). The proximate of yellowfin tuna bone meal indicated the best treatment at 110 oC with water content, ash content, protein content, fat content, calcium content were 9.27%, 59.7%, 12.65%, 7.75% and 20.47% respectively. The heavy metal (Cu, Pb, and Cd) and microbial analyzed was safe category according SNI for all treatments.